A bifunctional luminescent europium–organic framework for highly selective sensing of nitrobenzene and 4-aminophenol. Issue 71 (21st September 2017) - Gao, Ming-Liang; Cao, Xiao-Man; Zhang, Yu-Yang; Qi, Mei-Hong; Wang, Shi-Ming; Liu, Lin; Han, Zheng-Bo
Abstract : A bifunctional luminescentEu-MOF can be applied as a highly selective and sensitive bifunctional luminescence sensor to detect NB and 4-AP through an energy competition mechanism with low detection limits of 5–70 ppm and 5–110 ppm, respectively. Abstract : A microporous hexanuclear europium cluster based MOF, (DMA)2 [Eu6 (μ3 -OH)8 (BPDC)6 (H2 O)6 ] n ·(solv) x (DMA = dimethylamine cation and H2 BPDC = [1, 1′-biphenyl]-4, 4′-dicarboxylic acid), can be applied as a highly selective and sensitive bifunctional luminescence sensor to detect nitrobenzene and 4-aminophenol through an energy competition mechanism. More interestingly, this MOF can detect nitrobenzene and 4-aminophenol with low detection limits of 5–70 ppm and 5–110 ppm, respectively.